Importance of preclinical research in the development of neuroprotective strategies for ischemic stroke. - Neuhaus, A; Rabie, T; Sutherland, B; Papadakis, M; Hadley, G; Cai, R; Buchan, A (American Medical Association, 2014)
IMPORTANCE: Preclinical stroke research has had a remarkably low translational success rate, and the clinical need for novel neuroprotective therapeutics has gone largely unmet, especially in light of the severe underuse of thrombolysis in acute ischemic stroke. OBJECTIVE: In this review, we aim to provide a brief overview of the commonly used stroke models, their merits and shortcomings, and how these have contributed to translational failures. We review some recent developments in preclinical stroke, providing examples of how improved study quality and the use of novel methods can facilitate translation into the clinical setting. EVIDENCE REVIEW: This is a narrative review of ischemic stroke neuroprotection based on electronic database searches, references of previous publications, and personal libraries. FINDINGS: The stroke research community has not been complacent in its response to criticism: preclinical stroke studies now demonstrate considerable rigor, standardization, and emphasis on minimization of experimenter bias. In addition, numerous innovative methods and strategies are providing novel avenues for investigating neuroprotection, as well as more extensive characterization of established models. CONCLUSIONS AND RELEVANCE: The improvements in preclinical stroke models and methods will make stroke research a good example for preclinical medicine, in general, and will hopefully instill greater confidence in the clinical community regarding which compounds are worthy of further investigation in a clinical setting.